Thermogravimetric catalytic pyrolysis of high-density polyethylene over iron modified chicken eggshell wastes - Balasundram, V.; Shameli, K.; Norazana, Ibrahim; Ruzinah, Isha; Aishah, Abdul Jalil, Mohd. Kamaruddin, Abd. Hamid (Elsevier Ltd, 2023)
Among the major concerns of our current world include the accumulation of plastic wastes and the exhaustion of petroleum resources. Efforts to resolve these issues have contributed to multiple research and alternatives to be explored. One of the attractive alternatives that have been approached is the pyrolysis of plastic wastes. The use of catalysts offers multiple advantages in pyrolysis and different types of catalysts have been investigated in recent years. The potential of discarded natural wastes is acknowledged and studies to use food waste as a catalyst are to be developed in this research. The main objective of this project is to investigate the pyrolysis of high-density polyethylene (HDPE) over iron (Fe) modified waste chicken eggshell (WCE) as the catalyst. The pyrolysis was conducted at a temperature of 30 – 700℃ via a Thermogravimetric analyzer (TGA). WCE was washed, dried, and calcined in the furnace at 900℃ for 4 h. Fe was loaded (5 wt%) on the calcined WCE via the incipient wetness impregnation (IWI) method. The catalyst to HDPE mass ratio was fixed at 1:1. For comparison purposes, the commercial calcium oxide (CaO), calcined WCE, and Hydrogen exchanged Zeolite Socony Mobil − 5 (HZSM-5) were utilised in the pyrolysis of HDPE. Catalytic pyrolysis of HDPE over WCE and CaO had almost completely degraded with mass loss of 99.50% and 99.83% respectively at Phase II followed by pyrolysis of HDPE (94.05%), HZSM-5 (77.50%) and Fe/WCE (31.40%) samples. Among tested catalytic samples, the WCE catalyst works best to degrade HDPE into the highest volatile matter which attributes to higher pyrolysis oil yield.